Orphan and Fatherless: Reinterpretation of Hadiths about Orphans Using A Socio-Historical Approach - Magdarianti, Vicky; Fatkhi, Rifqi Muhammad (Dirasah International Journal of Islamic Studies, 2025)
This study examines the reinterpretation of hadiths about orphans in relation to the phenomenon of fatherlessness in contemporary society through the perspective of Fazlur Rahman's double movement theory. In classical Islamic studies, an orphan is generally defined as a child who loses his father before reaching the age of puberty. However, modern social realities show that children who grow up without the presence of a father figure—whether due to divorce, labor migration, or emotional absenteeism—also experience similar social and psychological vulnerabilities. This study aims to examine how the ethical values contained in hadiths on orphans can be contextualized to address the challenges faced by fatherless children in modern society. This research uses a qualitative approach, employing the library research method, tracing hadith using the takhrij al-hadith method, conducting socio-historical analysis, and applying Fazlur Rahman's interpretation framework of the double movement. The results of the study show that the hadiths about orphans emphasize the principles of compassion, social responsibility, and protection of the rights of children in vulnerable conditions. Through the double movement approach, these principles can be extended not only to orphans in the classical sense but also to children experiencing fatherlessness. In addition, the concept of kafālah in Islam can be an ethical and institutional model in child protection by ensuring parenting, education, and emotional support without changing the identity of the child's nasab. This research contributes to the development of a more contextual hadith study while offering a normative perspective for strengthening child protection policies in contemporary Muslim society.